การจัดโปรแกรมสุขศึกษาโดยใช้แบบแผนความเชื่อด้านสุขภาพเพื่อป้องกันการดื่มเครื่องดื่มแอลกอฮอล์ของนักเรียนหญิงมัธยมศึกษาตอนต้น - ปัณณวิชญ์ ปิยะอร่ามวงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
This quasi-experimental research aimed to study the effects of health education program using the health belief model to prevent alcohol drinking of lower secondary school female students. The sample was 48 female secondary school students under the Secondary Educational Service Area Office One, Bangkok. The experimental group of 23 and a comparison group of 25 people were divided from 48. The experimental group received the health education program which applied Health Belief Model for four weeks. The program was composed of learning activities, health guidance and campaign activities for alcohol drinking prevention. The comparison group received regular health education instruction by their school. The instrument used to collect data was a self-administered questionnaire. Statistical analysis was performed using frequency, percentage, mean scores, standard deviation, t-test and F-test. Scheffe was employed to test the differences of pair wise comparison. The results showed that 1) After the experiment, in the experimental group, the mean scores of perceived susceptibility of drinking alcohol, perceived severity of drinking alcohol, perceived benefits of not drinking alcohol, perceived barriers of preventing from drinking alcohol and intended not to drink alcohol were found statistically significant differences from before experiment at the .05 level, and higher than the comparison group. 2) The mean scores of perceived susceptibility of drinking alcohol, perceived severity of drinking alcohol, perceived benefits of not drinking alcohol, perceived barriers of preventing from drinking alcohol and intended not to drink alcohol in the experimental group after experiment and follow-up were found statistically significant differences from before experiment at the .05 level, however, the mean scores between follow-up and after experiment were found no statistically significant differences.